Aplikasi Dewisita Pesona Wisata Di Jawa Tengah Berbasis Android - Ragil Wijianto; Yesti Nurdeviyanti (Informatics and Computer Engineering Journal, 2023)
Indonesia is one of the island country in the world. Many tourist destinations that can be developed in every region throughout Indonesia. Central Java Provice as one of the province that has a variety of attractions that can be used as a mainstay of income. The development of various kinds of new tourism in Central Java and the development of mobile technology is also growing very rapidly at this time. One operation that is widely used today on smartphones is Android. Apart from being a communication device, smartphones are also added features such as video management, images, documents and so on. Tourists will be able to use their smartphone to find out tourism information in Central Java practically. For this reason the author tries to make a Final Project about the Android-based DEWISITA application program. This application can make it easier for users to travel in Central Java Province. This application uses an online system, so users can open applications must be connected to the internet. It is expected that the Central Java tourism application can be developed to run on other operating systems (multi platform)